2011
DOI: 10.1039/c0cp02485f
|View full text |Cite
|
Sign up to set email alerts
|

Monomer, clusters, liquid: an integrated spectroscopic study of methanol condensation

Abstract: We have combined static pressure, spectroscopic temperature, Fourier transform infrared spectroscopy (FTIR), and small angle X-ray scattering (SAXS) measurements to develop a detailed picture of methanol condensing from a dilute vapor-carrier gas mixture under the highly supersaturated conditions present in a supersonic nozzle. In our experiments, methanol condensation can be divided into three stages as the gas mixture expands in the nozzle. In the first stage, as the temperature decreases rapidly, small meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 54 publications
0
35
1
Order By: Relevance
“…The experiments were conducted using the apparatus and techniques described in detail elsewhere (Laksmono et al 2011) and are summarized only briefly here. A figure of the flow system is available in the online supplementary material as Figure S1.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments were conducted using the apparatus and techniques described in detail elsewhere (Laksmono et al 2011) and are summarized only briefly here. A figure of the flow system is available in the online supplementary material as Figure S1.…”
Section: Methodsmentioning
confidence: 99%
“…While one of the cited papers does involve a Laval nozzle apparatus, 19 the intention of that study is not to produce a medium suitable for kinetic measurements. Rather, the cited study by Laksmono et al 19 is primarily looking to deliberately induce condensation, and as such they operate their Laval nozzle at far higher pressures than used in more traditional Laval kinetic studies, and their expansion is clearly not stable, with the temperature observed to steadily decrease with distance upon exit of the Laval nozzle. Therefore, the experimental conditions in the work of Laksmono et al 19 are far removed from the ones used in the work of Shannon, 4 Gómez Martín et al 3 and Antiñolo et al 2 The other papers involve a free jet expansion and are in no way analogous to the thermal conditions within a Laval flow.…”
Section: Experimental Indications Of Clusteringmentioning
confidence: 99%
“…SSNR specifically question whether Laval nozzles themselves promote condensation and cite three principal papers as evidence for this phenomenon [17][18][19] . While one of the cited papers does involve a Laval nozzle apparatus, 19 the intention of that study is not to produce a medium suitable for kinetic measurements.…”
Section: Experimental Indications Of Clusteringmentioning
confidence: 99%
See 1 more Smart Citation
“…The large cross section of the sulfur 2p photoemission process makes XPS well suited for monitoring the mean cluster size. Different from the spatial or temporal resolution offered in some studies (Paci et al 2004;Laksmono et al 2011;Pathak et al 2013;Ezell et al 2014), the cluster beam is probed at a fixed distance about 10 cm downstream from the nozzle neck, i.e., at a mature particle population.…”
Section: Introductionmentioning
confidence: 99%